Completion of a Specialized Master’s Programme (LLM) in International Arbitration as an Integral Part of the Professional Training of Future Arbitrators - Nahorna, Olha (Pedagogical Discourse, 2019)
The article substantiates the necessity to complete a specialized Master’s programme in international arbitration as an integral part of the professional training of future arbitrators. Thus, some pessimists state that Master degree is not an option. Among other things, such facts are mentioned: arbitration practice area is not that big, so graduates can be frustrated when searching for a job; international arbitration is very popular among foreign students who are eager to take LLMs and spend huge sums of money on education, for example, in the US, an LLM from a top law school can cost up to US 60,000, excluding living expenses, Queen Mary’s LLM fees are around US 24,000, etc.; involvement of many adjunct faculty members with caseloads who cannot devote enough time and attention to their students; possibility to be enrolled on an arbitration-focused summer course. However, it is proved that general legal training is not able to provide a future specialist with the necessary theoretical knowledge, skills and abilities for practical activity in the field of international arbitration. It is noted that before choosing a university and a relevant Master’s programme one should not only analyze the curriculum and find out the number of credits that are devoted to the study of arbitration, but also pay attention to other important information, in particular, the leadership of a programme and faculty staff, cooperation with international arbitration institutions, possibility of internship, level of employment of graduates, etc. These factors influence the reputation and prestige of a selected Master’s programme. The list of the most authoritative LLM programmes in international arbitration is proposed, compiled as a result of the research conducted by the journal Global Arbitration Review in 2012.